Synthesis of Ternary Nanocomposites of MnO2/PANI/Maxsorb and their Performance as an Electrode Material for Supercapacitors - Aprilianti Nur'aini; Imam Prasetyo; Teguh Ariyanto (Directorate for Research and Innovation (DRI) ITB, 2025)
Increasing performance of supercapacitors can be achieved by using a composite of electrode materials. Nevertheless, selecting appropriate materials and determining the optimal combination composition remain significant challenges. In this research, a ternary composite of MnO2/polyaniline (PANI)/Maxsorb was studied. The combination of Maxsorb, PANI, and MnO₂ is a unique feature of this research, with Maxsorb acting as a porous structural framework; PANI enhancing electrical conductivity; and MnO₂ providing high pseudocapacitance. The ternary material was prepared by impregnation of MnO2 and PANI into the pores of Maxsorb carbon in a two-sequence procedure, i.e., (i) incipient wetness impregnation of Mn(NO3)2 into porous carbon followed by calcination to obtain MnO2/Maxsorb, and (ii) in situ polymerization of aniline monomer in the MnO2/Maxsorb, hence obtaining the final ternary nanocomposite of MnO2/PANI/Maxsorb. The electrochemical test using H2SO4 electrolyte (1 M) revealed that the ternary material outperformed single porous carbon or PANI as well as their binary nanocomposite in terms of properties such as energy density, power density, and capacitance. The ternary material had a specific surface area of around 2,078 m2 g-1, containing microporous and mesoporous structures. The material featured a specific capacitance up to 500 F g-1 and a power density of 37.6 kW kg-1 as well as an energy density of 62.69 Wh kg-1.